Prevalence of Blindness and Visual Impairment in Pakistan: The Pakistan National Blindness and Visual Impairment Survey - Jadoon, Mohammad Z; Dineen, Brendan; Bourne, Rupert R. A; Shah, Shaheen P; Khan, Mohammad A; Johnson, Gordon J; Gilbert, Clare E; Khan, Mohammad D; on behalf of Pakistan National Eye Survey Study Group (Investigative ophthalmology & visual science, 2006)
To determine the prevalence of blindness and visual impairment in adults aged 30 years and older in Pakistan and to assess socio-demographic risk factors. Multistage, stratified (rural/urban), cluster random sampling, with probability proportional-to-size procedures, was used to select a nationally representative, cross-sectional sample of adults 30 years of age or older. Each subject was interviewed; had visual acuity measured (logMAR; logarithm of the minimum angle of resolution); and underwent autorefraction, biometry, and fundus-optic disc examination. Those with less than 6/12 acuity in either eye underwent a detailed ophthalmic examination, including corrected distance visual acuity measurement and dilated ophthalmoscopy. A nationally representative sample of 16,507 adults (95.5% of those enumerated) was examined. The age- and gender-standardized prevalence of blindness was 2.7% (95% confidence interval [CI], 2.4%-2.9%). It has been estimated that there are 1,140,000 (962,000-1,330,000) blind adults in Pakistan (2003 statistics). Blindness prevalence varied throughout the country, being highest in the provinces of Punjab and Baluchistan and lowest in the North West Frontier Province. Rural areas had a higher prevalence of blindness than did urban areas (3.8% vs. 2.5%, P < 0.001). Increasing age and being female were significantly associated with presenting visual acuity of <6/60 (odds ratio [OR], 2.5; 95% CI, 2.3-2.7 and 1.3; 95% CI, 1.1-1.5, respectively). Educational status was also associated with presenting visual acuity of <6/60. Subjects who had attended primary school were 60% (P < 0.001) less likely to have acuity of <6/60 than were subjects who had never been to school. This comprehensive survey provides reliable estimates of the prevalence of visual impairment and blindness in Pakistan. A significant excess of visual impairment was found among the elderly and the uneducated. After adjustment for age differences, women were found to have a significant excess of severe visual impairment and blindness. Regional variations in the prevalence of blindness were also identified.